2016
DOI: 10.4103/1658-354x.168804
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopes for placement of double lumen tubes: Is it time to say goodbye to direct view?

Abstract: The advances in thoracic procedures require optimum lung separation to provide adequate room for surgical access. This can be achieved using either a double-lumen tube (DLT) or a bronchial blocker (BB). Most thoracic anesthesiologists prefer the use of DLT. However, lung separation in patients with potential difficult airway can be achieved using either BB through a single lumen tube or placement of a DLT over a tube exchanger or a fiberoptic bronchoscope. Numerous videolaryngoscopes (VL) have been introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The glottic view was significantly better and the need of external laryngeal manipulation significantly lower with the McGrath ® MAC VL as seen in the other studies. [1617] There was no significant difference between either of the laryngoscopes for the number of attempts taken to successfully intubate the trachea with a DLT with only one case in each group requiring two attempts at intubation.…”
Section: Discussionmentioning
confidence: 98%
“…The glottic view was significantly better and the need of external laryngeal manipulation significantly lower with the McGrath ® MAC VL as seen in the other studies. [1617] There was no significant difference between either of the laryngoscopes for the number of attempts taken to successfully intubate the trachea with a DLT with only one case in each group requiring two attempts at intubation.…”
Section: Discussionmentioning
confidence: 98%
“…Although prior studies showed that videolaryngoscopes might provide an improvement in the intubation condition with a high success rate [9], there were many indicators for evaluating devices for DLT intubation, and it was challenging to identify the best device in the absence of a review study to distinguish these devices in terms of applicability in these special circumstances. We conducted network meta-analysis, in which multiple treatments are being compared, to assess the effectiveness, with regard to factors such as success rate of the first attempt of intubation, intubation time, and adverse event rates of intubating devices (Mc, SV, CV, and stylet V) as a strategy for selecting the right device for DLT intubation.…”
Section: Introductionmentioning
confidence: 99%
“…This observation was similar to El Thahan et al . [ 11 ] and could be due to the steeper learning curve to learn DLT insertion with video laryngoscope.…”
Section: Discussionmentioning
confidence: 99%